Effect of Sales Growth, Firm Size, Profitability on Firm Value with CSR Moderation - Nurul Fatikhah R Izzati; Nanik Wahyuni (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Firm value is an important indicator used by investors to assess a company’s performance and future prospects, which is generally reflected in stock price movements in the capital market. In recent years, the agricultural sector has shown fluctuations and a decline in firm value, indicating the need to examine the determinants influencing this condition. This research examines the influence of sales growth, company scale, and profitability on corporate value, alongside the moderating effect of CSR over the 2020–2024 period. The research adopts a quantitative method using secondary data obtained from annual reports and sustainability reports of agricultural companies listed on the Indonesia Stock Exchange. From a population of 25 firms, 8 companies were selected using purposive sampling. The data were analyzed using panel data regression and Moderated Regression Analysis (MRA). The results indicate that firm size has a significant effect on firm value, while sales growth and profitability do not show significant effects. Furthermore, CSR is found not to moderate the relationship between sales growth and firm size on firm value, but it weakens the influence of profitability on firm value. Overall, these findings highlight the importance of integrating financial and non-financial factors in enhancing firm value within the agricultural sector.